Fabricating Cu(In, Ga)Se2 (CIGS) thin films with large grains based on the quaternary CIGS targets. (December 2017) - Peng, Xiao; Zhao, Ming; Zhuang, Daming; Sun, Rujun; Zhang, Leng; Wei, Yaowei; Lv, Xunyan; Wu, Yixuan; Ren, Guoan
Abstract: H2 Se gas is able to enhance the grain size of CuInSe2 near the surface and have limited effects on the grains inside the thin films. The thickness of the high qualified crystal layer (HQCL) near the surface has connection with Cu content of the thin film. Increasing the Cu content can effectively enhance the length of HQCL. To enhance the crystallinity of Cu(In, Ga)Se2, the 1600 nm-thickness CIGS thin films were fabricated by bilayer annealed strategy, where the first annealed layer CIGS is 1100 nm with the Cu content of 0.97 and the second 600 nm-thickness annealed layer CIGS with the Cu content of 0.82. Our results show that the bilayer annealed 1600 nm-thickness CIGS thin films have better crystallinity than the single layer annealed 1600 nm-thickness ones. Cells based on the bilayer annealed CIGS have higher current density and the conversion efficiency is up to 13.0%, much higher than 10.5%, which is the single layer annealed CIGS solar cells. Highlights: H2 Se atmosphere can enhance the grain size of CuInSe2 near the surface. The thickness of high qualified crystal layer can be enhance by increasing the Cu content of CuInSe2 . Bilayer annealing strategy can enhance the cell efficiency and the crystallinity of CIGS thin films.